Guidance and Counseling Evaluation Models during the COVID-19 Pandemic: Which is the most effective? - Ach. Sudrajad Nurismawan; Findivia Egga Fahruni; Ela Nur Fadilah; Surya Adhi Nugraha (Hasanuddin University, 2022)
This article aims to (1) map the evaluation models of guidance and counseling plans that counselors have implemented during the COVID-19 pandemic; (2) describe the fundamental concepts of evaluation models that are considered efficient and effective to be applied by counselors during the COVID-19 pandemic; (3) explain the practical procedures for an effective and efficient evaluation model to be applied by counselors during the COVID-19 pandemic. This article uses a literature study method to analyze the Miles & Huberman model on the latest relevant articles. It is hoped that the results will be by the article’s purpose. The results of the analysis of this article show that the guidance and counseling evaluation models used by counselors during the pandemic are four examples of the CIPP evaluation program, one evaluation model of the gap model, one evaluation model based on technology media, and six formative-summative evaluation models. Of the several evaluation models, there are two evaluation models that researchers recommend for counselors to use during the pandemic, namely the CIPP and gap evaluation models.